Investigating the Role of the Islamic Culture Course Syllabi in Infusing Islamic Tolerant Moral Values among University students: Staff Members' Perspectives at King Khalid University - Alwadai, Mesfer Ahmed Mesfer; Alhaj, Ali Albashir Mohammed (Technium Social Sciences Journal, 2023)
The present research aspires to scrutinize the role of the Islamic culture course syllabi in infusing Islamic tolerant moral values among university students from the perspectives of staff members at King Khalid University. Also, the study pointed to probing the degree to which the Islamic culture course syllabi infuse Islamic tolerant moral values among university students. The quantitative and qualitative research methods with the survey method were taken by the two researchers. Moreover, the two researchers developed an opinion poll of fifteen items based on a five-point Likert Scale that was analyzed quantitatively by applying descriptive data. The two researchers chose a random stratified sample from different campuses of King Khalid University in Abha, Algraa, Alomhalah, Dhahran Aljanoub, and to mention a few). The purposive sample of the study consists of hundred staff members. The results revealed that the general average of the role played by the Islamic culture course syllabi in infusing Islamic tolerant moral values among university students from the perspectives of staff members at King Khalid University came to a high degree with an arithmetic average of (4.17). Also, the findings demonstrated that the content of the Islamic culture syllabus better’s university students’ moral and intellectual capacity and prevents them from extremism, and ideological conflicts. The study recommends the requirement to carry out further investigations on the role of Islamic culture course syllabi courses on other variables such as character internationalization and advancement of work ethics among students.